Aspect processing across languages: A visual world eye-tracking study - Minor, Serge; Mitrofanova, Natalia; Guajardo, Gustavo; Vos, Myrte; Ramchand, Gillian (Frontiers in Language Sciences, 2023)
The study employed a combination of a picture selection task and Visual World eye-tracking to investigate the processing of grammatical aspect (perfective vs imperfective) in three languages: Russian, Spanish and English. In order to probe into the cognitive representations triggered by the aspectual forms we contrasted visual representations of different temporal portions of telic events – a snapshot of the process stage (ongoing event) and a snapshot of the immediate aftermath of the event/the result state (completed event). In all three languages, the gaze patterns and offline responses revealed a strong preference for representations of ongoing events in the imperfective condition. This confirms that the imperfective forms in all the three languages draw attention to the in-progress portion of a telic event. In the perfective condition, however, we found robust differences. Our results suggest that perfective telic verbs in Russian strongly highlight the result state of an event. In Spanish, the past perfective (Preterite) form also highlights event completion, but to a lesser extent than in Russian – in line with its less restrictive semantics in not requiring an inherent boundary. In contrast to Russian and Spanish, English speakers dit not show a preference for representations of completed events in the perfective (Simple Past) condition. This suggests that the English Simple Past form does not encode a preferential cognitive salience for either the activity portion of an event or its result state, and lends support to the analysis of the English Simple Past as a non-aspectual tense form.